(untitled) (Cadernos de Sociomuseologia, 2024)
Drawing from the installations and immersive works that Portuguese artist Túlia Saldanha (1930-1988) developed in the 1970s, considering the socio-cultural context of their production, and addressing different temporalities, this article analyses the multiple ways those works explored the experience of the participants. The article questions, furthermore, the relevance of these artworks when revisited, presented or reproduced in current times. Keywords: Túlia Saldanha, Installation, Participation